Positive association between fibrinogen-to-albumin ratio and preeclampsia risk in pregnant women of advanced maternal age: implications for clinical risk assessment - Wang, Nuoni; Liu, Shihao; Duan, Xiaoqin; Xie, Hui; Ge, Liangqing; Huang, Sulan (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPreeclampsia is a serious hypertensive disorder unique to pregnancy, with increased prevalence among women of advanced maternal age (AMA). Given the central role of inflammation and vascular dysfunction in the development of preeclampsia, this study aimed to evaluate the relationship between the fibrinogen-to-albumin ratio (FAR) multiplied by 100 (FAR × 100) and risk of preeclampsia in this high-risk group.MethodsA retrospective cohort of 2,296 pregnant women of advanced maternal age (≥35 years) was analyzed. The exposure variable, FAR × 100, was calculated as fibrinogen (g/L) divided by albumin (g/L) and multiplied by 100. PE was diagnosed based on the established clinical criteria. Participants were grouped into tertiles according to FAR × 100 levels. Both crude and adjusted logistic regression models were used to assess associations. Nonlinear relationships were assessed using restricted cubic spline (RCS) analysis, and subgroup analyses were conducted based on maternal characteristics.ResultsThe average age was 37.8 ± 2.7 years, with a preeclampsia prevalence of 14.3%. A higher FAR × 100 score was significantly associated with increased odds of developing preeclampsia. In the fully adjusted model, each unit increase in FAR × 100 raised the likelihood of preeclampsia by 8% (odds ratio [OR] = 1.08; 95% confidence interval [CI]: 1.06–1.10; p < 0.001). Compared to the lowest tertile, participants in the highest tertile had a significantly elevated risk (OR = 1.56; 95% CI: 1.11–2.19). The positive association between FAR × 100 and preeclampsia remained consistent across the subgroups, including those stratified by body mass index (BMI), red cell distribution width (RDW), gravidity, and family history of hypertension, with no evidence of a significant interaction.ConclusionFAR × 100 is independently associated with preeclampsia among women of AMA and may serve as a low-cost practical biomarker for early clinical risk stratification in prenatal care.